VERTICAL FLUX OF ICE ALGAL CELLS DURING THE ICE MELTING AND BREAKING PERIODS IN SAROMA KO LAGOON, HOKKAIDO, JAPAN (18th Symposium on Polar Biology) - タグチ, サトル; サイトウ, ヒロアキ; ハットリ, ヒロシ; シラサワ, クニオ; TAGUCHI, Satoru; SAITO, Hiroaki; HATTORI, Hiroshi; SHIRASAWA, Kunio (National Institute of Polar Research, 1997)
P(論文) The vertical flux of ice algae was determined with a multiple sediment trap at 4 m depth at the central station in Saroma Ko lagoon, Hokkaido, Japan. Collection was done in 5-day intervals from March 1 to April 24, 1994. The sea ice started breaking at the end of that period, from April 10 to 14,1994 and disappeared completely from the lagoon on April 17, 1994. The average fluxes of CHLa, PHEO, POC, PON, and BioSi during the melting season of sea ice were 20±6.5 mg CHLa, 2.0±1.0 mg PHEO, 630±190 mg C, 110±39 mg N, and 490±170 mg Si m^<-2> d^<-1>, respectively. The average % loss rates, determined by the ratio of the average vertical flux to the average ice algal production estimated from the standing stock and the growth rate, was calculated as 100% d^<-1> for CHLa during the ice melting period. Once the sea ice started breaking and disappeared, they increased by at least 1.5 fold. A relatively high increase was observed for PHEO (2.5 fold) and BioSi (2.3 fold) compared to the lowest increase of CHLa (1.5 fold). This implies that either the vertical flux of CHLa has been depressed due to unfavorable physical conditions, such as low salinity produced by a combination of melting sea ice and runoff of fresh water and exposure to high light provided by a disturbed position of broken sea ice, or the vertical flux of BioSi has been accelerated through physical breakage of ice algal cells by heterotrophic grazing and possibly resuspension of PHEO-rich water induced by wind forced mixing, evidenced by a significant increase of PHEO under the ice free water. Wind-forced resuspension should be considered in any study of vertical flux of ice algae when sea ice disappears in shallow water. departmental bulletin paper